Bioavailability of Trace Elements in Beans and Zinc-Biofortified Wheat in Pigs - Carlson, Dorthe (Humana Press Inc, 2012)
The objectives of this experiment were to study bioavailability of trace elements in beans and wheat containing different levels of zinc and to study how the water solubility of trace elements was related to the bioavailability in pigs. Three wheat and two bean types were used: wheat of Danish origin as a control (CtrlW), two Turkish wheat types low (LZnW) and high (HZnW) in zinc, a common bean (Com), and a faba bean (Faba). Two diets were composed by combining 81 % CtrlW and 19 % Com or Faba beans. Solubility was measured as the trace element concentration in the supernatant of feedstuffs, and diets incubated in distilled water at pH 4 and 38°C for 3 h. The bioavailability of zinc and copper of the three wheat types and the two bean-containing diets were evaluated in the pigs by collection of urine and feces for 7 days. The solubility of zinc was 34–63 %, copper 18–42 %, and iron 3–11 %. The zinc apparent digestibility in pigs was similar in the three wheat groups (11–14 %), but was significantly higher in the CtrlW+Faba group (23 %) and negative in the CtrlW+Com group (−30 %). The apparent digestibility of copper was higher in the HZnW (27 %) and CtrlW+Faba (33 %) groups than in the CtrlW (17 %) and LZnW (18 %) groups. The apparent copper digestibility of the CtrlW+Com diet was negative (−7 %). The solubility and digestibility results did not reflect the concentration in feedstuffs. The in vitro results of water solubility showed no relationship to the results of trace mineral bioavailability in pigs.